2021
DOI: 10.1007/s00338-020-02038-x
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress differentially impacts key calcification mechanisms in reef-building corals

Abstract: Coral reefs are increasingly threatened by climate change, mass bleaching events and ocean acidification (OA). Coral calcification, a process that is critical to build and maintain the structure of tropical coral reefs, is highly sensitive to both warming and acidifying oceans. However, in contrast to the impacts of OA on coral calcification, significant knowledge gaps remain regarding how coral biomineralization mechanisms are impacted by heat stress and bleaching. Using a combined physiological and geochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
2
8
1
Order By: Relevance
“…However, our results are based on relatively few data following this stress event, limiting the significance of these changes (Figure S6a in Supporting Information ); similar analyses of additional stress events would clarify these patterns and improve interpretations of calcification and skeletal geochemistry following thermal stress and bleaching. Nevertheless, these results are consistent with other recent studies demonstrating acute impacts of thermal stress on pH cf and skeletal geochemistry (Cheung et al., 2021; Clarke et al., 2017, 2019; D’Olivo & McCulloch, 2017; D’Olivo et al., 2019; M. T. McCulloch et al., 2017; Guillermic et al., 2020; Ross et al., 2017; Schoepf et al., 2021).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, our results are based on relatively few data following this stress event, limiting the significance of these changes (Figure S6a in Supporting Information ); similar analyses of additional stress events would clarify these patterns and improve interpretations of calcification and skeletal geochemistry following thermal stress and bleaching. Nevertheless, these results are consistent with other recent studies demonstrating acute impacts of thermal stress on pH cf and skeletal geochemistry (Cheung et al., 2021; Clarke et al., 2017, 2019; D’Olivo & McCulloch, 2017; D’Olivo et al., 2019; M. T. McCulloch et al., 2017; Guillermic et al., 2020; Ross et al., 2017; Schoepf et al., 2021).…”
Section: Resultssupporting
confidence: 90%
“…Similar reductions in DIC cf upregulation are observed during other warm extremes in the modern record, whereas DIC upregulation is highest during warm periods in the fossil record. Our results therefore add to the growing body of work identifying adverse effects of thermal stress and bleaching on coral CF chemistry under ocean warming (Cheung et al., 2021; Dishon et al., 2015; D’Olivo & McCulloch, 2017; D’Olivo et al., 2019; Schoepf et al., 2015, 2021). The changes in DIC upregulation identified here imply that extreme thermal stress undermines coral health via photosynthetic reductions that coincide with weak upwelling (and thus feeding capacity); together, these changes deprive the colony of the energy needed to drive the Ca‐ATPase pump and/or other active pathways (e.g., other alkalinity pumps or paracellular transport) that upregulate pH cf , leaving them more susceptible to regional changes in DIC sw and pH sw .…”
Section: Resultssupporting
confidence: 61%
“…Furthermore, if pH i in corals is regulated more tightly than extracellular body fluids (pH e ) during stress, as it is in other marine invertebrates (Tresguerres et al, 2020), the interactive effects of temperature stress and hypercapnia on pH i and pH e regulation may be particularly detrimental for biomineralization, which occurs in extracellular pockets of fluid located between the coral epidermis and the skeleton. Indeed, recent work has found that heat stress impairs coral regulation of calcifying fluid pH e with concurrent declines in calcification (Guillermic et al, 2021;Schoepf et al, 2021), which raises the question of whether coral pH i maintenance may be occurring at the expense of pH e during stress. Because the dynamics and mechanisms of acid-base regulation differ greatly between species and cell types (Tresguerres et al, 2017(Tresguerres et al, , 2020, it is critical that future work describes the molecular mechanisms that dictate these organismal responses to climate change stressors in order to better predict their ability to acclimatize and adapt to the ongoing climate crisis.…”
Section: Heat Stress Differentially Alters Intracellular Ph and Impairs Cellular Acidification Resilience In Bleaching-resistant And Bleamentioning
confidence: 99%
“…The potential effects of heat stress on acid–base regulation pose a particular challenge for maintaining coral calcification, as biomineralization is highly pH‐dependent (Barott et al, 2020; McCulloch et al, 2012; Venn et al, 2011, 2012). Indeed, recent studies have found that temperature stress alters the pH of the external calcifying fluid and depresses calcification (Guillermic et al, 2021; Schoepf et al, 2021), highlighting the need to better understand the physiology of coral climate change responses across biological scales.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effects of acidification on corals have commonly focused on calcification [ 15 , 16 , 17 , 18 , 19 ], growth [ 20 , 21 , 22 ], physiology [ 23 , 24 , 25 ], and phenotype [ 26 , 27 ], with only a few studies reporting that acidification is associated with coral bleaching [ 28 , 29 ]. Indeed, a large body of literature has demonstrated that global warming affects the coral community [ 30 , 31 ], and its health [ 32 , 33 , 34 ], metabolism [ 33 , 35 , 36 , 37 ], and calcification [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%